KEUNGGULAN BERSAING DITINJAU DARI GREEN MARKETING, SIKAP KONSUMEN DAN KUALITAS PRODUK (STUDI PADA INDOMILK SURAKARTA) - Muhammad Ainun Najib; Istiatin Istiatin; Ratna Damayanti (ITB AAS INDONESIA Surakarta, 2020)
The research aims to find out and describe the influence of simultaneously or partial green marketing, attitude and product quality towards competitive advantage in Indomilk Surakarta. This methodology research using quantitative descriptive research. The population was all consumers Indomilk Surakarta is unknown number. The number of samples was determined with the formula Lemeshow and the result 100 respondents. Sampling method using convenience sampling. The questionnaire used for data retrieval. Data analysis technique used was statistic analysis is multiple linier regression, F test, t test and determination coefficient. This test results the green marketing, attitude and product quality simultaneously and significance effect on competitive advantage in Indomilk Surakarta. Green marketing influential positive and significance effect against the competitive advantage in Indomilk Surakarta. Attitude influential positive and significance effect against the competitive advantage in Indomilk Surakarta. Product quality influential positive and significance effect against the competitive advantage in Indomilk Surakarta. Keywords : Competitive Advantage, Green Marketing, Attitude, Product Quality